Endocervical Adenocarcinoma in Young Woman: Case Report - Soares, Sílvia; Sousa, Rita; Figueiredo, Anabela; Agapito, Paula; Fernandes, Graça; Castro, Lígia (Citotech Online - Case Review, 2016)
The incidence of endocervical adenocarcinoma is increasing, especially in women aged between 20 and 30 years. The increased incidence, according to recent studies, may be due to persistent HPV infections associated with endogenous and exogenous risk factors. The treatment of this cancer may require a total hysterectomy with consequent infertility and psychological trauma. This paper aims to draw attention to the development of adenocarcinoma in young women, and in addition, it is intended to reflect on the factors that may be associated with the appearance of this pathology and the causes related with late diagnosis, in order to avoid radical therapeutic actions. To this end, a clinical case is reported, following a screening cytology, of a 30 years-old woman with cytological diagnosis of atypical glandular cells not otherwise specified (AGC, NOS), that was sent to the Cervical Pathology Unit of the reference hospital. The second cytology has diagnosed endocervical adenocarcinoma, later confirmed histologically.